2020
DOI: 10.12659/msm.922253
|View full text |Cite
|
Sign up to set email alerts
|

Exosomes Mediated Transfer of Circ_UBE2D2 Enhances the Resistance of Breast Cancer to Tamoxifen by Binding to MiR-200a-3p

Abstract: Background Circular RNA UBE2D2 (circ_UBE2D2) has been found to be involved in the progression of breast cancer. Exosomes are critical mediators of intercellular communication, however, the function of exosomal circ_UBE2D2 in breast cancer remains vague. Material/Methods Cell viability was measured by Cell Counting Kit-8 assay. Western blot was used to detect the levels of estrogen receptor alpha (ERα), E-cadherin, vimentin, CD9, and CD63. Migrated and invaded cells were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
45
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(47 citation statements)
references
References 33 publications
1
45
0
1
Order By: Relevance
“… 33 Moreover, Hu et al found that exosome-derived circ_UBE2D2 promoted resistance of breast cancer to tamoxifen via regulating miR-200a-3p. 34 Circ-XIAP has been found to be upregulated and promoted proliferation and migration in PCa. 20 However, the roles of exosomal circ-XIAP in DTX resistance of PCa have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“… 33 Moreover, Hu et al found that exosome-derived circ_UBE2D2 promoted resistance of breast cancer to tamoxifen via regulating miR-200a-3p. 34 Circ-XIAP has been found to be upregulated and promoted proliferation and migration in PCa. 20 However, the roles of exosomal circ-XIAP in DTX resistance of PCa have not been reported.…”
Section: Discussionmentioning
confidence: 99%
“…Besides, exosomes have attracted wide attention for the new means of intracellular communication (25,26). Through selectively packaging, secreting, and transferring ncRNAs between cells, tumor-derived exosomes could participate in the numerous hallmarks of breast cancer, including proliferation, metastasis, and drug resistance (17,27,28). Of note, exosomal circRNAs have been a hot research area for their important role in various human cancers (29)(30)(31).…”
Section: Discussionmentioning
confidence: 99%
“…Eight days after the injection, the mice were administrated with 20 mg/kg lapatinib (the sh-NC + Lapatinib group and the sh-circ-MMP11 + Lapatinib group) or the same amount of PBS (the sh-NC group and the sh-circ-MMP11 group) every three days. Tumor volume was measured at the indicated time points (8,11,14,17,21, and 23 days). Some 23 days after treatments, the tumors were obtained, followed by a photograph, weight, and analysis with RT-qPCR assay.…”
Section: Tumor Xenograft Assaymentioning
confidence: 99%
“…This result confirmed that hsa_circ_0025202 could be a therapeutic target in patients with hormone receptor-positive BC receiving TAM therapy. Additionally, circ_UBE2D2 was upregulated in TAM-resistant BC tissues and cell lines while circ_UBE2D2 deletion mitigated TAM resistance in BC cells (Hu et al, 2020 ). Circ_UBE2D2 was also significantly loaded in resistant cell-derived exosomes and could be transferred to parental cells.…”
Section: Circrnas In Bc Drug Resistancementioning
confidence: 99%